Personality profile of high-performing leaders: a BFI-2 analysis - Cristian PANAIT (Bulletin of "Carol I" National Defense University)
The present study employs a Big Five Inventory-2 (BFI-2) analysis to investigate the personality traits of a group of high-performing leaders operating within a military context. The Big Five Inventory-2 (BFI-2),T-score analysis, and Variance analysis (ANOVA) were utilized to identify the personality configurations contributing to effective leadership in military environments. The findings indicate that “Emotional Stability” and “Conscientiousness” are the most salient traits, with high scores for “Productivity,” “Responsibility,” and low “Emotional Volatility.” These traits, essential for goal-oriented behaviour and resilience under stressful conditions, are in accordance with previous research, linking these traits to job performance and stress management in leadership roles. A moderate level of Extraversion and Agreeableness is beneficial for maintaining normal team dynamics and fostering trust. Similarly, a balanced level of Openness to Experiences is associated with strategic adaptability without compromising discipline and performance. The study validates the utility of the BFI-2 in identifying personality traits that are predictive of success in exercising leadership in high-stress environments; it also highlights the distinction between leaders and the mean of the general population on these traits. The results indicate that the enhancement of these traits may result in increased leadership effectiveness, thus providing insights for the improvement of human resources selection and training programs.